A taxonomic revision of the genus Puccinia on Lycieae, a tribe of Solanaceae. (4th July 2018) - Otálora, Mónica A. G.; Berndt, Reinhard
ABSTRACT: We present a taxonomic and phylogenetic study of Puccinia species (rust fungi) infecting tribe Lycieae (Solanaceae), with focus on the New World taxa. Phylogenetic analyses using nuclear (nuc) rDNA 5.8S-ITS2 (ITS2) and mitochondrial (mt) cytochrome oxidase subunit 3 ( CO3 ) show that Puccinia species occurring on Lyciae are grouped in two major lineages, one New World and one Old World. We assessed the value of morphological traits and geographic range as important features for discriminating lineages. The morphology of teliospore pedicels and rust geographic ranges explained the relationships within this Puccinia species group. Four Puccinia species are recognized on Lycieae in the New World lineage and four in the Old World lineage. Puccinia tumidipes from North America is resurrected and P. dimidipes described as new from South America. In addition, P. spinulosa from Madagascar is reduced to a synonym of P. engleriana . Descriptions and a dichotomous key are presented for the accepted species.